Gambaran Pengetahuan dan Keterampilan Kader Dalam Pemantauan Pertumbuhan Bayi dan Balita di Wilayah Kerja Puskesmas Desa Lalang Tahun 2014 - Ria Sutiani; Zulhaida Lubis; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
The results of growth monitoring which is not appropriate can lead to the wrong interpretation of nutritional status and so do in making decisions to solve it. The success of these activities related to the cadres qualifications including their knowledge and skills in performing their duties. This study aimed to determine the knowledge and skills of cadres in monitoring the growth of infant and under five children in Puskesmas Desa Lalang. This research is an analytical study with cross sectional approach. The knowledge of cadres was measured by using a questionnaire, while their skills by the observation sheet. The population in this study was 155 cadres while the sample of 62 cadres chosen purposively. Data analysis was performed by using frequency distributions, while the correlation between knowledge and skills of cadres by Chi-square test (CI = 95%). The results showed that 80,6% of cadres had knowledge in good category and 66,1% of them has less skilled in carrying out their duties. There was a significant correlation between knowledge and skills of cadres in growth monitoring of infant and under five children (p = 0,046). Based on the results it can be concluded that growth monitoring of infant and under five children has not been performing optimally because of many cadres has less skills although their knowledge is good. It is suggested that health workers can held the training with practice methods than lecturing method so that good knowledge of cadres can be applied into action to improve their skills. Cadres are suggested to following the training which is organized by Puskesmas and applying their information obtained in the action when carrying out their duties at Posyandu.